Republic of Lithuania : Statistical Appendix and Tax Summary. (IMF Staff Country Reports; Country Report ;, 2001)
The paper provides the IMF's projections and estimates on Lithuania's basic data; gross domestic product by sector at current and constant prices; gross domestic product by expenditure at current and constant prices; monetary survey; deposit money banks, during 1995-99; supply and use of energy; electricity production and consumption; during 1994-99; summary of consolidated general government operations; interest rates on treasury bills and at commercial banks; indicators of financial sector vulnerability, 1997-2000; summary of the tax system, and so on.